The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.3390/nu10091328
|View full text |Cite
|
Sign up to set email alerts
|

Platycodon grandiflorum Saponins Ameliorate Cisplatin-Induced Acute Nephrotoxicity through the NF-κB-Mediated Inflammation and PI3K/Akt/Apoptosis Signaling Pathways

Abstract: Although cisplatin is a potent chemotherapeutic agent against cancers, its clinical application is seriously limited by its severe side effects of nephrotoxicity. Previous studies reported that saponins isolated from the roots of Platycodon grandiflorum (PGS) exerted protective effects in various animal models of renal injury, with no confirmation on cisplatin-induced injury. This study was designed to investigate the protective effect of PGS (15 and 30 mg/kg) on cisplatin-induced kidney injury in mice. The le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 51 publications
(52 reference statements)
1
33
0
Order By: Relevance
“…Furthermore, the results of histopathological examination and Tunel assay revealed that cP aggravated kidney damage compared with the con group. The present results were consistent with those from previous studies (38). In the present study, Dex administration significantly inhibited the production of serum Bun and Scr and reversed the alterations in body weight and ri.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Furthermore, the results of histopathological examination and Tunel assay revealed that cP aggravated kidney damage compared with the con group. The present results were consistent with those from previous studies (38). In the present study, Dex administration significantly inhibited the production of serum Bun and Scr and reversed the alterations in body weight and ri.…”
Section: Discussionsupporting
confidence: 94%
“…However, treatment with cP + dex + atip had a similar effect to cP alone; the expression levels of p-PI3K and p-AKT were significantly decreased in the cP + dex + atip group, indicating that the effects of dex were partially blocked by the α2ar antagonist. Furthermore, a previous study reported that aKT signaling is critical for recovery from renal ischemia-reperfusion injury, and that dex activates aKT via α2ar-dependent and -independent Pi3K coupling (38). Similarly, dex exerts neuroprotective (46), cardioprotective (28) and lung-protective effects (30,47) via activation of the Pi3K/aKT signaling pathway.…”
Section: Discussionmentioning
confidence: 96%
“…Determinations of nuclear factor‐κB (NF‐κB), IL‐1β, and TNF‐α were performed using kidney homogenate with the aid of specific ELISA kits (Diaclone Research, France) as per the guidelines of the manufacturer .…”
Section: Methodsmentioning
confidence: 81%
“…Natural compounds from herbs or medicinal plants are widely used for therapy and prevention of kidney diseases 16,17 . Ginseng, the root of Panax ginseng C.A.…”
Section: Introductionmentioning
confidence: 99%